2007
DOI: 10.1002/macp.200700239
|View full text |Cite
|
Sign up to set email alerts
|

Atom‐Transfer Radical Copolymerization of Furfuryl Methacrylate (FMA) and Methyl Methacrylate (MMA): A Thermally‐Amendable Copolymer

Abstract: Polymers of furfuryl methacrylate (FMA) are interesting materials because of the presence of the furfuryl group as the reactive diene functionality in the pendent group. Copolymers of FMA and MMA were prepared using atom‐transfer radical polymerization (ATRP) catalyzed by CuCl, in combination with HMTETA as a ligand at 90 °C. It was very difficult to prepare by conventional radical polymerization because of several side reactions involving the reactive diene group. The copolymer composition was calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…In our previous work the DSC measurements and the self-healing studies of the copolymers P(AMA-co-FMA-co-MIMA) revealed that the variation of the chain length of the co-monomers influenced the temperature of the retro-Diels-Alder reaction: More nonpolar environments resulted in higher temperatures of the retro-Diels-Alder reaction [20]. This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28].…”
Section: A N U S C R I P Tsupporting
confidence: 53%
See 1 more Smart Citation
“…In our previous work the DSC measurements and the self-healing studies of the copolymers P(AMA-co-FMA-co-MIMA) revealed that the variation of the chain length of the co-monomers influenced the temperature of the retro-Diels-Alder reaction: More nonpolar environments resulted in higher temperatures of the retro-Diels-Alder reaction [20]. This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28].…”
Section: A N U S C R I P Tsupporting
confidence: 53%
“…The first investigations on the synthesis of PFMA via ATRP and free radical polymerization (FRP) and the copolymerization with methyl methacrylate (MMA) were published by Kavitha and Singha as well as the synthesis of a PFMA-b-PEHA-b-PFMA triblock copolymer. The authors also studied the self-healing properties of the copolymer [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] polymeric materials that have excellent mechanical properties and are thermally remendable. [9] Interestingly, there are only a few examples in the literature that involve polymers appended with maleimides towards fabrication of thermoreversible materials.…”
Section: Thermoreversible Crosslinked Materialsmentioning
confidence: 99%
“…The reversibility of DA reaction is widely applied to the preparation of remarkable polymers. Thermallyreversible DA reactions have been used in numerous studies including polymer synthesis from multifunctional monomers [4,[7][8][9][10][11][12][13][14][15] or by cross-linking of functional copolymers containing maleimide or furan pendant groups [16][17][18][19][20][21][22], surface modifications [16,23], organic-inorganic polymer hybrids [24,25], reversible crosslinking polymer chains/ gels [5,16,24,26] and remendable/self-healing polymers [11,12,27]. Due to the fact that these reactions can proceed under mild conditions without a catalyst, this makes them attractive for designing covalently reversible bonds in which furan and maleimide functional groups are responsible for association and dissociation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%